2008
DOI: 10.1080/00071660802302203
|View full text |Cite
|
Sign up to set email alerts
|

Relation between social order and use of resources in small and large furnished cages for laying hens

Abstract: 1. The objective was to determine the relation between social rank and use of resources in a small furnished cage with sufficient resources per hen (SF) and a commercial large one with less adequate allowance of facilities per hen (LF). 2. Ninety-two cross layers were used. At the age of 16 weeks, the hens were divided at random into two groups. There were 4 furnished cages with 5 birds per cage and 4 large furnished cages with 18 birds per cage. The dominance hierarchy was determined, in which highest, medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…(2017) and Rierson (2011), who reported that poultry spent time in all given lighting environments during the preference test, no matter if it was a preferable lighting environment or not. Previous research have proved that dominant hens had priority use of resources, for example feeders, nest box and dust bath, resulting in subordinate hens not being able to use the facilities fully (Weeks and Nicol, 2006; Shimmura et al ., 2008). Specifically, in this experiment, birds with lower social hierarchy occasionally waited in a less desirable lighting environment until the birds with higher social hierarchy left the adjacent compartment, which may be part of the reason why poultry also spent time in less preferable environments.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) and Rierson (2011), who reported that poultry spent time in all given lighting environments during the preference test, no matter if it was a preferable lighting environment or not. Previous research have proved that dominant hens had priority use of resources, for example feeders, nest box and dust bath, resulting in subordinate hens not being able to use the facilities fully (Weeks and Nicol, 2006; Shimmura et al ., 2008). Specifically, in this experiment, birds with lower social hierarchy occasionally waited in a less desirable lighting environment until the birds with higher social hierarchy left the adjacent compartment, which may be part of the reason why poultry also spent time in less preferable environments.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdale modulates ventral striatum, thus the lesion of amygdale in juveniles affected social development [23] and personal (social) distance [24]. Domestic chicks' diversified socio-emotional behavior has been frequently reported such as pecking and flapping in group like 'play' [25] or isolated context with panic calls [26]. Cholinergic and other neurotransmitter systems control chick basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…In furnished cages, the quality of the resources, such as dust bath, may be more important than the cage floor area. Limited resources lead to competition, as well as behavioral restriction, which results in increased aggressive interactions and mortal-ity (Shimmura et al 2007a(Shimmura et al , 2008c(Shimmura et al , 2009). As mentioned above, these scores as a whole were supported by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also a small number of scientific declarations that such separation is difficult. For example, the scientific declaration 'aggressive interactions were increased by decreased litter area' (Shimmura et al 2007a(Shimmura et al , 2008c(Shimmura et al , 2009) cannot be separated but should be attached to one measurement: 'litter floor'. Therefore, in this study, some measurements were not separated by behavioral/ motivational systems.…”
Section: (3) Selection Of Measurementsmentioning
confidence: 99%